How much can we rely on a scrambled COVID-19 vaccine? It is not the only way out! - Nikunja Kumar Das; S Prasanna; Priyanka Pandit; Vaibhav Laxmikant Dudhat (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
The COVID-19 pandemic has engulfed the world in the blink of an eye and created a state of panic. Vaccine is one of the suggested ways to counter the menace. Smallpox was an ideal vaccine candidate yet, it took about 182 years to eradicate. Vaccines are associated with incidents of mishap like the “Cutter incident”. COVID-19 vaccine has a political, commercial angle to it, with at least 62 vaccine candidates in the pipeline. Potential obstacles in development of vaccines are mutations in strains of SARS-CoV-2, lack of details of biological properties of the virus and incomplete information of pathogenicity, lack of suitable animal models. The potential side effects of the vaccine are eosinophilic infiltration, increased infectivity following challenge infections, antibody-dependent enhancement of infections. The general public has to stop anticipating that a vaccine is nearby and believe that for now, vaccine is face mask, hand wash, and social distancing and hope that either the virus goes weak or an effective vaccine arrives rather early than late.